Selective monocellular necrosis of Hodgkin's/Reed-Sternberg cells and their immunoreactivity to human serum antinuclear antibodies in NS- and MC-types of malignant lymphogranuloma - Kodousek, R; Tichá, V; Tichý, M (Neoplasma, 1992)
The selective (apoptotic) necrosis of Hodgkin's cells in malignant lymphogranuloma appears to be etiologically quite different from focal one due to ischemic-vascular causes. The morphology and supposed etiopathogenesis of this cellular lesion, as well as the karyoclastic process-presumably apoptotic in nature-are briefly described and considered as a mechanism leading to cellular regression with subsequent destructuralization and release of DNA-reactive nucleoprotein material in form of free hematoxylin bodies. An original observation of the immunoreactivity of Hodgkin's cells with antinuclear antibodies of human serum in a case of collagenosis is also described.
Keywords: buňky Reedové-Sternberga; Hodgkinova nemoc; mužské pohlaví; nekróza; ženské pohlaví; Necrosis; antinukleární protilátky; dospělí; Humans; Reed-Sternberg Cells; Adult; Female; Hodgkin Disease; Antibodies, Antinuclear; lidé; Male